Food as a human right: ethical and bioethical perspectives (Research, Society and Development, 2021)
The search for development goes through human dignity, in what is essential to man, food, being necessary to think of new forms and productive processes that consider nature as an essential good. Thinking about sustainability is thinking about a more equitable and egalitarian society, ensuring healthier and more dignified ways of life. Thus, the research aimed to understand the dimensions involved in what is essential to human beings, the act of eating, reflecting on the means of production and consumption considering the capitalist-based economy. The work was developed through bibliographic methodology, using scientific articles, data from research institutes and social organizations, as well as laws and guidelines on the theme, food security. As a result, the research confirmed that, despite the current legislation, treaties, and national and international agreements, the problem of hunger remains a very present reality, and effective actions are needed from society and the state to make food an inalienable human right.